Polaritonic-to-Plasmonic Transition in Optically Resonant Bismuth Nanospheres for High-Contrast Switchable Ultraviolet Meta-Filters - Alexander Cuadrado; Johann Toudert; Rosalia Serna (IEEE Photonics Journal)
In the quest to unveil alternative plasmonic elements overcoming noble metals for selected applications in photonics, we investigate, by numerical simulations, the near ultraviolet (UV)-to-near infrared optical response of solid and liquid Bi nanospheres embedded in a dielectric matrix. We also determine the resulting transmission contrast upon reversible solid–liquid phase transition to evaluate their potential for switchable optical filtering. The optical response of the solid (liquid) Bi nanospheres is ruled by localized polaritonic (plasmonic) resonances tunable by controlling the diameter. For a selected diameter between 20 and 50 nm, both solid and liquid nanospheres present a dipolar resonance, inducing a strong peak extinction in the near UV, however, at different photon energies. This enables a high transmission contrast at selected near UV photon energies. It is estimated that a 2-D assembly of 30-nm solid Bi nanospheres with a surface coverage of 32% will almost totally render extinct (transmission of 2%) a near UV 3.45-eV (359 nm) light beam, whereas upon phase transition, the resulting liquid Bi nanospheres will show a transmission of 30%. This paper is appealing for the fabrication of locally reconfigurable optical metamaterials for integrated switchable near-UV optics.